Analysis of the Influence of Knowledge, Work Procedures and Technology on Employee Performance - Presilawati, Febyolla; Murni, Mirza; Balqis, Fudja Devani (Universitas Bina Sarana Informatika, 2024)
The purpose of this study is to determine the influence of Knowledge, Work Procedures and Technology on Employee Performance at the Aceh Transportation Office both partially and simultaneously. This research method is by testing hypotheses using multiple linear regression analysis, F test (simultaneous) and t test (partial) intended to determine the influence of the independent variable on the dependent variable at a confidence level of 95% (α = 0.05). The object of this study is Knowledge, Work Procedures and Technology on Employee Performance at the Aceh Transportation Office The sample size of this study is as much as 96 employees. Research data were collected through questionnaires and documentation studies. The results showed that simultaneous tests between the variables of Knowledge, Work Procedures and Technology affect the Performance of Employees at the Aceh Transportation Office. Then partially, Knowledge affects the Performance of Employees at the Aceh Transportation Office. Work Procedures affect the Performance of Employees at the Aceh Transportation Office. Then partially, namely Technology affects the Performance of Employees at the Aceh Transportation Office.